Trends in the incidence of common sexually transmitted infections at the global, regional and national levels, 1990–2021: results of the Global Burden of Disease 2021 study - Miao Deng; Jiaxi Chen; Zhi Wang; Rubin Zheng; Wenyi Pang; Rui Sun; Zhixun Bai (Tropical Medicine and Health)
Abstract Background Sexually transmitted diseases (STDs) are prevalent globally and represent a significant public health challenge. This study aims to evaluate the most recent estimates of the burden of common sexually transmitted infections (STIs) at global, regional, and national levels, which will aid in the development of more effective prevention strategies. Methods Data for this study were obtained from the Global Burden of Disease (GBD) 2021 study via the Global Health Data Exchange (GHDx) query tool ( https://vizhub.healthdata.org/gbd-results/ ). We extracted the data in accordance with GBD operational guidelines, selecting the most recent results from the 2021 GBD study. The latest GBD study results provided data on incidence, prevalence, and disability-adjusted life years (DALYs) for 21 regions and 204 countries. We extracted the number of cases, incidence, and age-standardized incidence of sexually transmitted diseases (STDs) by sex, age group, and location, following GBD usage guidelines. The data were categorized into five groups based on sociological demographic indices (SDIs). Results In 2021, the total number of STDs was ~ 289.17 million, reflecting an increase of about 58.38% compared to 1990. While the total number of cases was higher in males, the increase was more pronounced in females. Syphilis exhibited the highest age-standardized rate (ASR) in Equatorial Guinea (EAPC 0.57, 95% CI [− 2.97, 4.24]). Trichomoniasis had the greatest ASR in Tanzania (EAPC − 1.24, 95% CI [− 4.97, 2.64]). Gonococcal (EAPC − 0.52, 95% CI [− 4.33, 3.44]) and chlamydial infections (EAPC − 0.52, 95% CI [− 4.33, 3.44]) showed the highest ASR in South Africa, while genital herpes (EAPC − 1.3, 95% CI [− 4.89, 2.44]) had the greatest ASR in Zimbabwe. HIV/AIDS had the highest ASR in Lesotho (EAPC − 0.33, 95% CI [− 3.99, 3.46]), and the combined ASR for HIV/AIDS and STIs was highest in South Africa (EAPC − 0.47, 95% CI [− 0.58, 0.37]). Conclusion The burden of STDs remains high and has been steadily increasing; the burden of STIs is more severe in low SDI areas and among young and middle-aged people; the prevalence, incidence, and disability-adjusted years of STIs during the period 1990–2021 are attributable to three main factors: population, disease epidemiology, and aging.